2017
DOI: 10.1080/10942912.2017.1301954
|View full text |Cite
|
Sign up to set email alerts
|

Triacylglycerol composition, melting and crystallization profiles of lipase catalysed anhydrous milk fats hydrolysed

Abstract: Dairy products remain valuable components of human diet due to their balanced nutritive value and pleasant flavour. In this study, triacylglycerols (TAGs) from anhydrous milk fats were hydrolysed by Lipozyme-435 and Novozyme-435 and later on analysed by using ultra performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry. Results revealed that the percentages of TAGs (CN 28-34) and TAGs (CN 36-42) with at least two short-chain fatty acids and with short-and medium-chain fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…403 Another example is the hydrolysis of triacylglycerols from anhydrous milk catalyzed by Novozym-435 to decrease the percentage of two short or medium chain fatty acids while the percentage of triglycerides with at least two long-chain fatty acids (CN 44-54) enhanced the melting and crystallization profiles of the product. 404 In another instance, hydrolysis of oils by using some organic co-solvents produced a monophasic system that reached 88% using N435, while using Lipozyme TL-IM or Lipozyme RM-IM the reaction reached only 66%. 405 N435 and Thermomyces lanuginosus lipase were compared in the hydrolysis of anhydrous milk cow fat or anhydrous buffalo milk fat using ultrasonic microwave-assisted extraction to eliminate short chain fatty acids.…”
Section: Food Technology: Glyceride Modifications and Productionmentioning
confidence: 99%
“…403 Another example is the hydrolysis of triacylglycerols from anhydrous milk catalyzed by Novozym-435 to decrease the percentage of two short or medium chain fatty acids while the percentage of triglycerides with at least two long-chain fatty acids (CN 44-54) enhanced the melting and crystallization profiles of the product. 404 In another instance, hydrolysis of oils by using some organic co-solvents produced a monophasic system that reached 88% using N435, while using Lipozyme TL-IM or Lipozyme RM-IM the reaction reached only 66%. 405 N435 and Thermomyces lanuginosus lipase were compared in the hydrolysis of anhydrous milk cow fat or anhydrous buffalo milk fat using ultrasonic microwave-assisted extraction to eliminate short chain fatty acids.…”
Section: Food Technology: Glyceride Modifications and Productionmentioning
confidence: 99%
“…corn silage, sesame meal) and is associated with increased milk yield, milk fat and milk protein concentrations, and with benefits such as increase of digestibility, more stable ruminal pH, and decreased risk of acidosis [28], but not with specific changes in the FAs profile of the microbial flora of the rumen. Recently it was shown that cyclopropane fatty acids, which occur in milk fat as minor component, can be used as markers for silage feeding [29] and an enzymatic hydrolyzation provoke reduction of short and medium fatty acids and increase of long fatty acids which could produce differences in the physical proprieties of FA profiles [30].…”
Section: Introductionmentioning
confidence: 99%
“…The results of DSC analysis can be used to describe the kinetics and mechanism of crystallization (melting/crystallization temperature, specific heat capacity, and, indirectly, the polymorphism of fat crystals). [28,29] During the DSC analysis, samples of UMF and MF fractions were first melted within a temperature range of −40°C to +40°C, and then they were crystallized within a temperature range of +40°C to −40°C at a rate of 5°C min −1 . Examples of melting and crystallization thermograms for UMF and MF fractions are presented in Figure 4.…”
Section: Crystallization and Melting Curves (Dsc Analysis)mentioning
confidence: 99%